My Beloved is Mine and I am His: A Literary Analysis of Loyalty, Responsibility, and Intimacy in Song of Songs 2:16 - Pattinaja, Aska Aprilano (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2025)
The marital crises in contemporary society increasingly expose the fragility of commitment, intimacy, and mutual responsibility within husband–wife relationships. Against this backdrop, this study aims to examine Song of Songs 2:16 as a biblical text that articulates an alternative paradigm of exclusive and reciprocal marital intimacy. Employing a literary method and exegetical analysis of the Hebrew text, this research focuses on the poetic structure, key lexical expressions, and relational imagery within the verse. The analysis shows that the reciprocal phrase "My beloved is mine, and I am his" sets up a covenantal model of relationship in which closeness is based on mutual belonging, exclusive faithfulness, and shared responsibility. Furthermore, the image of the beloved as “who grazes among the lilies” underscores the husband’s active role as a caring and responsible presence in the relationship. This study concludes that Song of Songs 2:16 provides a deep and helpful framework for today's marriages, pushing back against modern ideas of commitment that depend on conditions by basing marital closeness on a belief in unconditional, shared, and responsible belonging.